PENGARUH BAKTERI ENDOFITIK DAN Azolla pinnata TERHADAP POPULASI BAKTERI ENDOFITIK, KANDUNGAN N, DAN BOBOT KERING P PADI (Oryza sativa L.) PADA TANAH BERSALINITAS - Melani, Melani; Saribun, Daud Siliwangi; Setiawati, Mieke Rochimi (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2017)
Nitrogen deficiency is the main problem of rice growth in salt stress condition. Endophytic bacteria has an ability to enhance the number of available N in plant tissue by fixing N from the atmosphere, meanwhile Azolla pinnata has high content of N that can increase the available N in soil. The aim of this research was to know the limit of salinity stress tolerance in rice with application of endophytic bacteria and A. pinnata on enhancing the population of endophytic bacteria, N content, and dry weight of rice on soil with salinity. The research was conducted on March 2016 until March 2017 at the Green House of Ciparanje Universitas Padjadjaran. Samples were analized at the Laboratory of Soil Biology and Laboratory of Soil Fertility and Plant Nutrion, Faculty of Agriculture, Universitas Padjadjaran. The design experiment used was single factor randomized block of 8 treatments and 4 repetitions. The treatments consist of with and without the application of endophytic bacteria and A. pinnata on soil with salinity of 0, 2, 4, and 6 mmhos cm-1. The results showed that the application of endophytic bacteria and A. pinnata gave the significant difference on the population of endophytic bacteria, N content, and dry weight of rice up to 4 mmhos cm-1.